2011
DOI: 10.1111/j.1524-4725.2011.01973..x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sirolimus in the Prevention of Cutaneous Squamous Cell Carcinoma in Organ Transplant Recipients

Abstract: Skin cancers are common in organ transplant recipients (OTRs). In this review, we discuss the epidemiology of and risk factors for cutaneous neoplasms, particularly squamous cell carcinoma (SCC) in OTRs. The pathogenesis of SCC is reviewed, as well as the potential mechanisms for tumor progression and metastasis associated with two commonly used immunosuppressive medications: tacrolimus and cyclosporine. Finally, we discuss the mechanism of action and potential preventative use of sirolimus, a member of a newe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Inhibitors of the mTOR, such as sirolimus and everolimus, have a unique role in immunosuppression after solid-organ transplantation. This is mainly due to their anti-proliferative properties [ 2 ] and also because they lack the tubular and vascular toxicity associated with calcineurin inhibitors. The use of mTOR inhibitors for routine maintenance immunosuppression, however, remains controversial and some recent studies did not demonstrate a survival benefit for mTOR-based regimes when compared with those relying on calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of the mTOR, such as sirolimus and everolimus, have a unique role in immunosuppression after solid-organ transplantation. This is mainly due to their anti-proliferative properties [ 2 ] and also because they lack the tubular and vascular toxicity associated with calcineurin inhibitors. The use of mTOR inhibitors for routine maintenance immunosuppression, however, remains controversial and some recent studies did not demonstrate a survival benefit for mTOR-based regimes when compared with those relying on calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoedema is a recognized adverse effect of mTOR inhibitors, which is surprisingly well described in the dermatology [ 2 ] and transplant [ 1 ] literature. In hindsight, we feel that the diagnosis could have been made earlier, which would have avoided unnecessary investigations and delay.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitors have been linked to higher incidences of cutaneous carcinoma. 35 Changing regimens to include sirolimus or everolimus may be beneficial in select patients. Sirolimus and everolimus are mammalian target of rapamycin inhibitors, which result in downregulation of ribonucleic acids (RNA) involved in cell cycle progression.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…These agents have potent antitumor activity and have been shown to be beneficial in OTRs with respect to cutaneous tumorigenesis. 35 A randomized clinical trial showed that conversion to sirolimus-based immunosuppression in renal transplant patients resulted in delayed development of premalignant skin conditions, a deceleration of the incidence of new NMSC, and even induction of regression of existing skin lesions. 36 This has recently been confirmed by another randomized clinical trial of 120 OTRs randomized to receive sirolimus or continue with calcineurin inhibitors by Euvrard et al They found a significantly longer duration of survival free of SCC in the sirolimus group, with new SCC diagnosed in 22% of patients receiving sirolimus versus 39% on calcineurin inhibitors.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…4,6 Some immunosuppressants, such as azathioprine, have been associated with dose-dependent increases in SCC, 4 whereas others, such as mycophenolate mofetil and sirolimus, have suggested protective effects. [7][8][9] Sirolimus is a macrolide that exerts its immunosuppressive effects by inhibiting the mammalian target of rapamycin, a member of the cellular phosphatidylinositol 3-kinase pathway that regulates cell proliferation, metabolism, survival, and angiogenesis and is upregulated in SCCs. 10 Among SOTRs, revision of the immunosuppressive regimen by conversion to sirolimus has been shown to prevent secondary SCC after initial SCC diagnosis.…”
mentioning
confidence: 99%